2014
DOI: 10.1128/aac.03605-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Highly Conserved Residues Involved in Inhibition of HIV-1 RNase H Function by Diketo Acid Derivatives

Abstract: Overall, we provide the first demonstration that RNase H inhibition by DKAs is due not only to their chelating properties but also to specific interactions with highly conserved amino acid residues in the RNase H domain, leading to effective targeting of HIV retrotranscription in cells and hence offering important insights for the rational design of RNase H inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 46 publications
5
82
0
Order By: Relevance
“…Although there is only one oxygen anion in the II‐26 structure that interacts with Mg 2+ , multiple additional interactions with Arg557 and His539 of such an oxygen and of the substituted benzene rings with Ala538 and Lys540 are predicted to contribute to increase the inhibitory activity of the compound. In agreement with our modeling studies, previous analyses predicted the involvement of ionic/π interactions between Arg557 and Mg 2+ ‐binding RNase H inhibitors (Poongavanam et al., ; Corona et al., ).…”
Section: Resultssupporting
confidence: 92%
“…Although there is only one oxygen anion in the II‐26 structure that interacts with Mg 2+ , multiple additional interactions with Arg557 and His539 of such an oxygen and of the substituted benzene rings with Ala538 and Lys540 are predicted to contribute to increase the inhibitory activity of the compound. In agreement with our modeling studies, previous analyses predicted the involvement of ionic/π interactions between Arg557 and Mg 2+ ‐binding RNase H inhibitors (Poongavanam et al., ; Corona et al., ).…”
Section: Resultssupporting
confidence: 92%
“…Moreover, spectroscopic analyses and molecular modeling studies indicated that such derivatives can mechanistically act by interfering with the two-metal ions through direct coordination of the metal cofactors in the enzyme catalytic site. This is in agreement with the behavior of diketo/triketoacid derivatives [14], but differs from what was observed for allosteric inhibitors [6,18] and dual inhibitors of RNase H and RT-associated DP activity, which were recently proposed to bind to a site close, but not coincident, to the RNase H active site [46]. Finally, calculated ADME properties and the preliminary finding that 10d displayed cellular cytotoxicity in human MT-4 cells at >7 μM, which was evaluated within the range of its inhibition concentration, predict that this compound can have desirable drug-like properties, thus making it suitable for further development.…”
Section: Discussionsupporting
confidence: 89%
“…The lack of RnhA, and the presence of RnhC as the sole RNase H1 in clinically relevant mycobacterial pathogens, fortifies the case for inhibitors of the RnhC endonuclease as potential anti-tuberculosis and anti-leprosy agents. [Prior attention to RNase H as a drug target has focused primarily on inhibitors of the RNase H component of HIV reverse transcriptase as potential antivirals for treatment of AIDS (3032). ] The M. smegmatis Δ rnh strains we have constructed, which rely on only RnhC or RnhA for growth, are suitable for cell-based screening for specific inhibitors of RnhC, i.e., by selecting small molecules that arrest growth of a rnhC + Δ rnhA strain but do not affect an rnhA + Δ rnhC strain.…”
Section: Discussionmentioning
confidence: 99%